Manual de controle patrimonial: uma contribuição à divisão de patrimônio da Universidade Federal Da Paraíba a partir do novo plano de contas aplicado ao setor público - Sousa, Fabiana Formiga de (2017)
This work had as objective to analyze the procedures of patrimonial control from the standardization of the accounting to the public sector. Firstly, to identify the changes in the structure of the chart of accounts applied to the public sector through various sources such as resolutions and normative instructions issued by the bodies involved the process of standardization of accounting and then was verified with the UFPB the existence of a Manual of Patrimonial Control. The second part of the paper was to propose a manual with the purpose of facilitating patrimonial control and contributing in a didactic way on the process of incorporation, movement and disincorporation of all the assets belonging to the UFPB, as well, with the aim of giving greater agility and reliability in the management information issued to the managers. Therefore, this technical work was relevant and its use will avoid future undue procedures that may cause damage to the UFPB, as well as that the Federal Audit Court (TCU) may issue another determination due to divergences between the data recorded in the Integrated System (SIAFI) and the inventory report of the movable assets, as was the case evidenced in accordion no. 408/2005 - TCU - first chamber. The research made it possible to verify that the form of patrimonial control existing in the UFPB needs improvement. And, therefore, the implantation of the model of Manual presented here is important and brings managerial benefits to the managers, besides knowing the value of the managed equity.